The Identity Construction of Young Gay on Instagram - Moekahar, Fatmawati; Amalia, Asrinda (Jurnal The Messenger, 2021)
In Indonesia in the last five years, homosexuals still experience discrimination. This condition causes the gay to create new identities that are constructed. Instagram is a medium that is currently widely used by gay in social interactions. This media is used by gays to construct their identity. This study aims to find out how they construct their identity through instragram social media, and what their identity is different in the real world and cyberspace in Bandung. This research method is qualitative with a phenomenological study approach. The informants in this study were gay groups in Bandung City, expecially gay young. Sampling technique used to purposive sampling with deep interview, observation and documentation. The results of this study say that one's experience of being gay is driven by internal environmental factors, namely the treatment of discrimination from family members, colleague and friends. The popular features of Instagram used by informants on Instagram are posting photo, video, and comment by share story to post. Gays construct their identity through online and offline media. Researchers found that there were two stages (front stage and back stage) played by gays when interacting with others.